DILECTINGS AS A PROJECT OF THE CONTEMPORARY TOOL FOR TEACHER'S DIGITAL LITERATURE EDUCATIONAL COMPETENCES - М. Каналс-Ботінес; І. Когут; А. Ралуй (Borys Grinchenko Kyiv Metropolitan University, 2022)
Abstract Statement of the problem. The article is devoted to highlighting the main provisions regarding the imple- mentation of the DILECTINGS project as a set of measures for all participants in the educational process digital literacy development Research method. There were used digital reading methods, remote work methods using DLL and LDR Hub, the use of eTwinning/School Education Gateway platforms to perform digital reading tasks, the use of CANVAS technologies. Data. Teachers developed the skills of pedagogical activities using digital reading technologies, working in Moodle and eTwinning/School Education Gateway. Students developed competencies in digital reading, use of technology to create video files. Conclusions. The implementation of DILECTINGS project had provide formation of narrow and specialized competences in the use of technical means in educational activities